MOOD AND MODALITY OF INTERPERSONAL MEANING IN RESEARCH JOURNAL ARTICLES - Ilham, Ilham (Eduscience : Jurnal Ilmu Pendidikan, 2019)
AbstractThis study aimed to analyze how mood and modality of interpersonal meaning are used in research journal articles published internationally. This study used qualitative approach by applying content analysis design. The data were taken from six research journal articles in three fields of study (Linguistic, English language teaching and Medical) written by English native and non-native writers. Theoretical sampling was applied to collect the number of research journal articles. The data of this study were one thousand nine hundred ninety two clauses analyzed using analysis table of mood consisting subject, finite and modal adjunct and modality consisting modalization and modulation. The findings of this study show the six research journal articles are informative and effectively use stated subject, past and present finite and possibility and usuality to deliver interpersonal meaning. These findings provide grammatical characteristics of mood and modality in international research journal articles.Ã‚Â keywords: mood, modality, interpersonal meaningÃ‚Â AbstrakPenelitian ini bertujuan menganalisis bagaimana mood dan modality dari makna interpersonal digunakan dalam artikel penelitian yang ditebitkan secara internasional. Peneitian ini menggunakan pendekatan kualitative dengan menggunakan analisisisi. Data penelitian ini diambil dari 6 artikel penelitian internasional di 3 bidang ilmu (Linguistik, Pengajaran Bahasa Inggris dan Kedokteran) yang ditulis oleh penutur asli bahasa Inggris dan bukan penutur asli. Sampling teoritis diterapkan untuk mengumpulkan jumlah artikel jurnal penelitian. Data penelitian ini terdiri dari seribu Sembilan ratus Sembilan puluh dua klausa yang dianalisis dengan menuggunakan table analisis mood yang terdiri dari subject, finite dan modal adjunct dan table analisis modality yang terdiri dari modalizasi dan modulasi. Hasil temuan penelitian ini menunjukan enam artikel jurnal penelitian bersifat informative dan secara efektif menggunakan subjek stated, finite past dan present dan possibilitas dan usualitas dalam menyampaikan makna interpersonal. Penemuan penelitian ini memberikan ciri-ciri gramatika dari mood dan modalitas dalam artikel jurnal internasional.Ã‚Â kata kunci: mood, modalitas, makna interpersonalÃ‚Â